Effects of modified tall oil and creatine monohydrate on growth performance, carcass characteristics, and meat quality of growing-finishing barrows - P R O'Quinn; B S Andrews; J C Woodworth; Robert D Goodband; John A Unruh; Jim L Nelssen; Michael D Tokach (Kansas Agricultural Experiment Station Research Reports, 1999)
A trial was conducted to evaluate the effects of modified tall oil (MTO; .50% of the diet) and creatine monohydrate (CMH; 25 g/pig/day for 10 days prior to slaughter) on performance, carcass characteristics, and meat quality of finishing barrows. Feeding MTO improved ADG and F/G during the growing phase and improved F/G over the entire trial and during the 10 day CMH loading period. Feeding MTO reduced backfat, but neither CMH nor MTO affected other carcass characteristics or meat quality measures at 24 h postmortem. These data suggest that MTO improves performance and reduces backfat with little effect on meat quality, whereas CMH does not appear to be beneficial to growing-finishing swine.; Swine Day, Manhattan, KS, November 18, 1999
Keywords: Swine day; 1999; Kansas Agricultural Experiment Station contribution; no. 00-103-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 841; Modified tall oil; Creatine monohydrate; Barrows; Meat quality